Kualitas Layanan Memediasi Pengaruh Kepercayaan Terhadap Kepuasan Pasien pada Aplikasi Telemedicine - Victorya, Jonathan; Winoto Tj, Hery; Tecoalu, Melitina; Wahyoedi, Soegeng (Syntax Corporation, 2024)
Background: The Covid-19 pandemic has led to a significant surge in the utilization of telemedicine applications. The measurement of the effectiveness and success of implementing telemedicine applications is demonstrated through patient satisfaction in their usage. Patient satisfaction is influenced by trust and service quality. Research on trust, service quality, and patient satisfaction in telemedicine is currently limited. Objective: This study aims to explore the relationship between trust and patient satisfaction mediated by service quality. Method: The research involves users of telemedicine applications who completed questionnaires. Data were analyzed using SmartPLS software. Results: The study included 128 respondents, with the majority of telemedicine users aged 18 to 25 years. Based on questionnaire results, most respondents agreed with questions regarding trust, service quality, and satisfaction in telemedicine usage. Model analysis revealed a significant relationship between trust, service quality, and patient satisfaction (P-value < 0.05; T-statistic > 1.96). Additionally, service quality played a mediating role in the influence of trust on patient satisfaction (P-value < 0.05; T-statistic > 1.96). Conclusion: Trust significantly influences service quality and patient satisfaction. Service quality also significantly affects patient satisfaction. Moreover, service quality acts as a mediator in the impact of trust on patient satisfaction